Teacher's Culture of Work (A Site Study at SD Kaligawe 1 Gayamsari, Semarang) - Purwanto, Purwanto (2011)
Objective of the research are to describe the characteristic of teacher's culture of work in learning activity and cooperation with school personnel at SD Kaligawe 1 Gayamsari, Semarang. It is a qualitative research with ethnography design. This research is conducted in that school. Human resources in this research are teacher, principal and vice principal. Data collection method used depth interview, observation, and documentation. Data analysis used interactive analysis model that stared (1) data reduction, (2) data display, and (3) drawing conclusion. Data validity is consisting of credibility, transferability, dependability, and conformability. The results of this research show that (1) teachers compile learning plan together in Teacher's Workgroup forum. In learning implementation of first, second and third grade used thematic learning, while in fourth, fifth, and sixth grade used subject system. In thematic learning, teachers compile learning material using spider web model. In learning activity the method that is used are lecture, question and answer, discussion and demonstration. Learning model generally used is contextual and cooperative learning model. In learning activity, teacher used approach that involves students to be active and antusiatic in learning activity and used experience in learning so that the teacher can understood the student's characteristic. (2) Teacher is involved in compiling school program, determining school policy and doing the policy. Teacher is also involved as member in subcommittee that is made by school to realize the school program. The teacher is actively given suggestion and input in compiling school program. To support the implementation of teaching learning activity, teacher is cooperating with principal, teacher, guidance and counseling teacher and other employee.